Global environment change, sociology, and paradigm isolation - Sunderlin, William D. (1995)
There are three broad categories of thought on how to respond to problems associated with global environmental change: structural economic change and grassroots mobilization; international diplomacy and regime building; and cultural/behavioural transformation. These categories of thought correspond to the classical paradigms of sociology –– that is, to the class, managerial, and pluralist perspectives. Many writings on global environmental change adhere to the tenets of one particular paradigm while ignoring, downplaying the significance of, or challenging the tenets of other paradigms. The article discusses the dangers of such compartmentalization and recommends that writers on global environmental change work to cross paradigm boundaries.